Vulcanization, static mechanical properties, and thermal stability of activated calcium silicate/styrene‐butadiene rubber composites prepared via a latex compounding method. Issue 2 (28th July 2021) - Wang, Weijiang; Zhang, Yinmin; Zhang, Yongfeng; Sun, Junmin
Abstract: Herein, we describe the latex compounding preparation of activated calcium silicate (ACS)/styrene‐butadiene rubber (SBR) composites aiming to improve filler dispersibility. The effects of ACS particle size and filler content on the vulcanization, static mechanical properties, and thermal stability of composite materials were evaluated. FT‐IR analyses showed that the rubber macromolecules were chemically adsorbed on the surface of the ACS particles, while SEM and TEM indicated that the ACS particles were uniformly distributed in the composites, and agglomeration occurred only at high filler content levels. ACS particle size reductions accelerated composite vulcanization, whereas increasing filler content had the opposite effect. ACS particles strengthened the mechanical properties of prepared composites, with marked increases in tensile strength and tear strength as ACS particle size decreased and filler content rose, reaching maximal values of 15.37 MPa (increased by 932%) and 45.91 kN/m (increased by 425%), respectively, at an ACS average particle size of 1 μm and 90 phr loading. ACS particle integration also enhanced composite thermal stability. These data indicate that ACS enhances rubber composites owing to the incorporation of well‐dispersed ACS particles into the rubber matrix, strong interactions between ACS particles and rubber molecules, and the thermal barrier effects of these particles. Abstract : In this manuscript, the authors integrate activated calcium silicate (ACS) with styrene‐butadiene rubber (SBR) to prepare rubber composites containing a certain amount of occluded rubber, which gives the resultant composite rigidity and enhances its mechanical properties and thermal stability, although the addition of large amounts of ACS inhibits the vulcanization process.